Graves‘ disease following vaccination against SARS-CoV-2: A systematic review of the reported cases - Konstantinos Katsikas Triantafyllidis; Konstantinos Katsikas Triantafyllidis; Panagiotis Giannos; Panagiotis Giannos; Dimitra Stathi; Dimitra Stathi; Konstantinos S. Kechagias; Konstantinos S. Kechagias (Frontiers in Endocrinology, 2022)
The newly developed COVID-19 vaccines have established a safe profile, yet some individuals experience a wide range of adverse events. Recently, thyroid dysfunction, including Graves’ disease, has been observed after administration of different COVID-19 vaccines, although causality remains a matter of debate. The aim of this systematic review was to examine the available literature and provide an overview of reported cases of Graves’ disease following COVID-19 vaccination. We identified 21 eligible articles which included 57 patients with Graves’ disease following COVID-19 vaccination. Fourteen participants were males (25%, 14/57) and 43 (75%, 44/57) were females with a mean age of 44.3 years. The most common presenting symptom was palpitations (63%, 27/43) followed by weight loss (35%, 15/43). The majority of patients received thionamides (47%, 25/53). The clinical status after treatment was provided for 37 patients and it was improved in the majority of them (84%, 31/37). Graves’ disease is possibly a condition clinicians may expect to encounter in patients receiving COVID-19 vaccines. While the above adverse event is rare, considering the scarcity of available data in scientific literature, and causality is not yet confirmed, the increased awareness of clinicians and the early recognition of the disorder are important for the optimal management of these patients.